Effects of TiO2 pillared montmorillonite nanocomposites on the properties of asphalt with exhaust catalytic capacity. (20th December 2018) - Jin, Jiao; Xiao, Ting; Tan, Yanqing; Zheng, Jianlong; Liu, Ruohua; Qian, Guoping; Wei, Hui; Zhang, Junhui
Abstract: Titanium dioxide (TiO2 ) pillared montmorillonite nanocomposites (T/M) have been prepared from montmorillonite (MMT) with tetrabutyl titanate by sol-gel method, and characterized by X-ray diffraction, transmission electron microscopy together with energy dispersive X-ray. Anatase TiO2 could be intercalated into the layer structure of MMT and dispersed on the outer surface, as the basal spacing increases by 0.26 nm for T/M. The influences of different contents of T/M on the properties of matrix asphalt and catalytic capacity for automobile exhaust were also investigated. T/M modified asphalt samples showed a remarkable increase on the G ∗ /sinδ and improved resistance of asphalt pavement to failure for improved high temperature rheological performances. And T/M could improve the resistance of asphalt to UV aging effectively. What' more, T/M modified asphalt samples showed superior degradation capabilities of NO, CO and HC for simulating the catalysis of actual automobile exhaust.